2016
DOI: 10.17305/bjbms.2016.1465
|View full text |Cite
|
Sign up to set email alerts
|

Nesfatin-1 alleviates extrahepatic cholestatic damage of liver in rats

Abstract: Obstructive jaundice (OJ) can be defined as cessation of bile flow into the small intestine due to benign or malignant changes. Nesfatin-1, recently discovered anorexigenic peptide derived from nucleobindin-2 in hypothalamic nuclei, was shown to have anti-inflammatory and antiapoptotic effects. This study is aimed to investigate the therapeutic effects of nesfatin-1 on OJ in rats. Twenty-four adult male Wistar-Hannover rats were randomly assigned to three groups: sham (n = 8), control (n = 8), and nesfatin (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
4
3
0
Order By: Relevance
“…In addition, protective effect of nesfatin-1 on gastric (11), intestinal (15), cardiac (17), cerebral (12) and dermal (10) damage was attributed to its role in supporting antioxidant capacity of the related tissues. However, in a cholestatic liver injury model, 10-day nesfatin-1 treatment has decreased hepatic MDA levels and hepatocyte necrosis without significantly altering the oxidative DNA damage (36). In parallel to their results, our data demonstrate that histopathologically verified alleviation of sepsis-induced hepatic injury by nesfatin-1does not appear to involve an antioxidant action, suggesting the presence of other anti-inflammatory mechanisms operating in the hepatic cells, which require further investigation.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, protective effect of nesfatin-1 on gastric (11), intestinal (15), cardiac (17), cerebral (12) and dermal (10) damage was attributed to its role in supporting antioxidant capacity of the related tissues. However, in a cholestatic liver injury model, 10-day nesfatin-1 treatment has decreased hepatic MDA levels and hepatocyte necrosis without significantly altering the oxidative DNA damage (36). In parallel to their results, our data demonstrate that histopathologically verified alleviation of sepsis-induced hepatic injury by nesfatin-1does not appear to involve an antioxidant action, suggesting the presence of other anti-inflammatory mechanisms operating in the hepatic cells, which require further investigation.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, the present study recorded that in the NTþnesfatin-1 group, nesfatin-1 notably elevated the serum levels of testosterone, LH and FSH, in addition to restoring the activities of the steroidogenic enzymes 3b-HSD and 17b-HSD. This might be ascribed to its anti-apoptotic, anti-inflammatory, antioxidant effects [7,8] and its stimulating effect on autophagy in testicular tissue, as shown in our results. It was reported that autophagy enhances the uptake of cholesterol into the Leydig cells; hence it activates the steroidogenic enzymes with subsequent increase of synthesis of testosterone [11].…”
Section: Discussionsupporting
confidence: 73%
“…As displayed in our results, nesfatin-1 treatment significantly restored the sperm parameters in NT-treated rats. The restoration of normal sperm parameters by nesfatin-1 might be explained by its antioxidant, anti-apoptotic, anti-inflammatory effects [7,8] and its stimulating effect on autophagy that has a prime role in the conservation of healthy sperms [43], as revealed in our results. The histopatholological analyses of the testicular tissue confirmed our aforementioned findings.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…101 Because of this, various antioxidants have been tested in experimental obstructive jaundice models. [102][103][104] Solmaz et al 105 found that nesfatin-1 reduced the oxidative damage of the liver through its anti-inflammatory and antioxidant effects, 105 and may become a potential drug for the treatment of obstructive jaundice.…”
Section: Other Diseasesmentioning
confidence: 99%